2012
DOI: 10.5433/1679-0359.2012v33n5p1907
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da diferença das temperaturas retal e do canal auditivo de acordo com a conformação da concha acústica em cães

Abstract: ResumoA termometria auditiva vem sendo utilizada para mensuração da temperatura em cães. Porém, existem diferentes conformações da concha acústica nesta espécie, sendo que orelhas pendulares podem alterar o microclima auditivo. Portanto, objetivou-se estudar a diferença das temperaturas retal e do canal auditivo de acordo com a conformação da concha acústica em cães. Foram utilizados 111 cães hígidos com orelhas ereta (grupo I), semipendular (grupo II) e pendular (grupo III) com 37 animais cada. A aferição da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
1
1
Order By: Relevance
“…Temperature and pH of the ear canal also responded similarly in all groups (Fig.1). These parameters are important for the establishment of pathogenic bacteria and/or fungi (Mueller et al 2012, Mueller et al 2013, but no correlation with infection was observed in our study. None the less, temperatures in all groups were slightly lower than normal, which is expected in patients suffering from external otitis (Yoshida et al 2002), infectious or otherwise.…”
Section: Discussioncontrasting
confidence: 78%
“…Temperature and pH of the ear canal also responded similarly in all groups (Fig.1). These parameters are important for the establishment of pathogenic bacteria and/or fungi (Mueller et al 2012, Mueller et al 2013, but no correlation with infection was observed in our study. None the less, temperatures in all groups were slightly lower than normal, which is expected in patients suffering from external otitis (Yoshida et al 2002), infectious or otherwise.…”
Section: Discussioncontrasting
confidence: 78%
“…The females from first to third parturition order were distributed into two environments, with natural and localized cooling ventilation. Rectal temperature was obtained utilizing a veterinary thermometer (± 0,1°C), measured during 3 minutes (Mueller et al, 2012). The respiratory rate was obtained through observation and counting of flank movements during 15 seconds, performing the correction to one minute.…”
Section: Methodsmentioning
confidence: 99%